Fractional Absorption of Active Absorbable Algal Calcium (AAACa) and Calcium Carbonate Measured by a Dual Stable-Isotope Method - Uenishi, Kazuhiro (MDPI, 2010)
With the use of stable isotopes, this study aimed to compare the bioavailability of active absorbable algal calcium (AAACa), obtained from oyster shell powder heated to a high temperature, with an additional heated seaweed component (Heated Algal Ingredient, HAI), with that of calcium carbonate. In 10 postmenopausal women volunteers aged 59 to 77 years (mean ± S.D., 67 ± 5.3), the fractional calcium absorption of AAACa and CaCO(3) was measured by a dual stable isotope method. (44)Ca-enriched CaCO(3) and AAACa were administered in all subjects one month apart. After a fixed-menu breakfast and pre-test urine collection (Urine 0), (42)Ca-enriched CaCl(2) was intravenously injected, followed by oral administration of (44)Ca-enriched CaCO(3) without carrier 15 minutes later, and complete urine collection for the next 24 hours (Urine 24). The fractional calcium absorption was calculated as the ratio of Augmentation of (44)Ca from Urine 0 to Urine 24/ augmentation of (42)Ca from Urine 0 to Urine 24. Differences and changes of (44)Ca and (42)Ca were corrected by comparing each with (43)Ca. Fractional absorption of AAACa (mean ± S.D., 23.1 ± 6.4), was distinctly and significantly higher than that of CaCO(3 )(14.7 ± 6.4; p = 0.0060 by paired t-test). The mean fractional absorption was approximately 1.57-times higher for AAACa than for CaCO(3). The serum 25(OH) vitamin D level was low (mean ± S.D., 14.2 ± 4.95 ng/ml), as is common in this age group in Japan. Among the parameters of the bone and mineral metabolism measured, none displayed a significant correlation with the fractional absorption of CaCO(3) and AAACa. Higher fractional absorption of AAACa compared with CaCO(3) supports previous reports on the more beneficial effect of AAACa than CaCO(3) for osteoporosis.